Heavy Metals Cd, Hg and Pb in Fresh Milk from Dairy Farms in South Jakarta Analyzed by ICP-MS - Silalahi, E. M.; Lioe, H. N.; Faridah, D. N. (Tropical Animal Science Journal, 2023)
Determination of heavy metals cadmium (Cd), mercury (Hg), and lead (Pb) in fresh milk refers to the FDA 2020 method by inductively coupled plasma mass spectrometry (ICP-MS) was verified in this study. The objective of this study was to evaluate the heavy metal concentrations in fresh milk produced by traditional dairy farmers in Jakarta, a metropolitan city, analyzed by the verified method. Ninety-four milk samples were collected from 18 dairy farmers in southern Jakarta, which is the concentrated location of traditional dairy farms in Jakarta nowadays. Wet digestion was performed using microwave digestion with the reagents 65% HNO3, 30% H2O2, and 30% HCl to extract these samples. The analytical performance of the method was as follows: linearity (R value ≥ 0.9975), precision (RSD range 7.66%–13.38%), recovery values (tested on 0.10 ng/g to 1.0 ng/g milk) at 88%-102%, limits of Cd, Hg, and Pb detections at 0.41 ng/g, 0.86 ng/g, and 1.20 ng/g respectively. The results showed that the heavy metals concentrations in fresh milk were obtained with a range of Cd from not detected (nd) to 1.92 ng/g, Hg from nd to 9.85 ng/g, and Pb from nd to 13.24 ng/g. The concentrations were below the national standards for Cd, Hg, and Pb in milk and milk products, and Pb was below the Codex standard for fresh milk. The results of rapid risk assessment on Cd and Hg in fresh milk are below the provisional tolerable monthly intake (PTMI) of Cd according to Joint FAO/WHO Expert Committee on Food Additives (JECFA 2023) and the provisional tolerable weekly intake (PTWI) of Hg according to JECFA 2011. Hence, the consumption of fresh milk in South Jakarta gave no health concern. Pb was not assessed due to no tolerable intake, according to JECFA.